Peninggalan Kerajaan Majapahit: Candi, Karya Sastra, Prasasti - Febriyanti, Intan; Susanti, Lr Retno; Hudaidah, Hudaidah (Estungkara: Jurnal Pengabdian Pendidikan Sejarah, 2024)
The legacy of the Majapahit Kingdom is a very important legacy for the development of culture and civilization in Indonesia. The founding of this kingdom is estimated to be in the thirteenth to sixteenth centuries, until it was known as the largest and most powerful kingdom in the archipelago. This article examines various aspects of Majapahit heritage, including architecture, art, literature, and government systems. Through analysis of artifacts such as temple remains, inscriptions and literary works, as well as their influence on local society and culture, this article was created to provide deeper knowledge about Majapahit's contribution to shaping the identity of the Indonesian nation. Apart from that, discussing the challenges of preserving these heritages in the modern era is also an important focus, considering the high historical value and tourism potential that can be developed. Thus, it is hoped that this article can increase awareness of the importance of preserving Majapahit's historical heritage for future generations.